Moderasi Beragama Dalam Kacamata Islam Dan Buddha (Analisis Komparatif) - Samsuri, Bisri; Askar, Ahmad (Jurnal Studi Agama, 2023)
Recently, the issue of religious moderation has become quite an interesting issue to discuss, in fact, this issue is expected to become the last bastion in caring for religion and nationality. Because every religion does not teach about violence and destruction, but teaches peace and harmony. Based on this background, researchers want to look at the concept of religious moderation from an Islamic and Buddhist perspective through comparative analysis. Regarding the results of this study. 1) Islam views religious moderation as maintaining balance, justice, tolerance in practicing faith and interacting with other people. Because with moderation, religion can create pillars of harmony, peace and harmony, both moderation in Aqidah, worship and social interaction. 2) Just as Islam teaches religious moderation, this is also the case in Buddhism. This is based on the teachings that Buddha taught containing dimensions of moderation, such as humanity, tolerance, and the teachings of non-violence. Thus, it can be concluded that there are similarities and differences regarding the concept of religious moderation in the two religions. The similarity is that they both have the view that moderate religion is the religious practice desired by both religions. Meanwhile, the difference is that in Islam the basis of religious moderation is balance, while in Buddhism it is love.